2022
DOI: 10.3390/antibiotics11101285
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Amphipathic β-Sheet Temporin-Derived Peptide with Dual Antibacterial and Anti-Inflammatory Activities

Abstract: Temporin family is one of the largest among antimicrobial peptides (AMPs), which act mainly by penetrating and disrupting the bacterial membranes. To further understand the relationship between the physical-chemical properties and their antimicrobial activity and selectivity, an analogue of Temporin L, [Nle1, DLeu9, DLys10]TL (Nle-Phe-Val-Pro-Trp-Phe-Lys-Phe-dLeu-dLys-Arg-Ile-Leu-CONH2) has been developed in the present work. The design strategy consisted of the addition of a norleucine residue at the N-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The main mechanism of action of AMPs is based on their interaction with the membrane of the pathogen [ 19 ]. Although the exact process is not yet fully defined, studies performed on model membranes (e.g., liposomes) have shown that the positive charge is responsible for the initial interaction with the negatively charged membrane of microorganisms, whereas the hydrophobic portion is responsible for their insertion into the lipid bilayer [ 20 ]. Consequently, achieving the right balance between the hydrophilic and hydrophobic domains is key in determining the specificity of action of AMPs [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism of action of AMPs is based on their interaction with the membrane of the pathogen [ 19 ]. Although the exact process is not yet fully defined, studies performed on model membranes (e.g., liposomes) have shown that the positive charge is responsible for the initial interaction with the negatively charged membrane of microorganisms, whereas the hydrophobic portion is responsible for their insertion into the lipid bilayer [ 20 ]. Consequently, achieving the right balance between the hydrophilic and hydrophobic domains is key in determining the specificity of action of AMPs [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD data suggest the formation of beta sheet structures in the presence of 1,2-dioleoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (DOPG)/cardiolipin (CL) and DOPG/1,2-Dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE) LUV. The increase in the hydrophobicity of the peptide due to the presence of NLe was related to an increased anti-inflammatory activity of the peptide in murine macrophage cell lines [ 99 ].…”
Section: Temporins From Ranamentioning
confidence: 99%
“…As well as showing possibilities for development into anti-infective agents for use against antibiotic-resistant and biofilmproducing microorganisms (Mangoni et al, 2016), temporin peptides have excited interest as a result of their anti-inflammatory (Zhang et al, 2021), antiviral (Marcocci et al, 2022), antiparasitic (André et al, 2020), wound healing (Di Grazia et al, 2014) and antidiabetic (Musale et al, 2018) properties. With the exception of the broad spectrum antimicrobial peptide temporin L (Bellavita et al, 2022), they display varying degrees of growth-inhibitory activity against Gram-positive bacteria and against the opportunistic yeast pathogens Candida spp. but are inactive against Gram-negative bacteria.…”
Section: Characterization Of Host-defense Peptides In L Palmipes Skin...mentioning
confidence: 99%